The relationship of nutrition literacy to nutrition status and differences by gender in Thai high school students - Pathan, Nutsima; Yangyuen, Suneerat; Somdee, Thidarat (Intelektual Pustaka Media Utama, 2025)
Nutrition literacy (NL) is an indicator of food consumption nutrition status, and the prevalence of overweight among high school students is increasing. Thus, there is a need for an analysis of nutrition literacy and other factors relevant to overweight, comparing differences based on biological sex and gender to prevent and reduce the risk of overweight among high school students. In this cross-sectional study. Boys represented 63.5% and girls 36.5% of the total. The prevalence of overweight in high school students was found to be 35.1% of all cases. The incidence of overweight was higher in high school student boys at 67.1%. The age range of boy and girl students was found a median of 17.50 years (16.30–18.80). NL was associated with overweight; the main NL protective factors in boys were knowledge of nutrition principles (AOR=0.03; 95% CI: 0.002–0.618; p=0.022), interactive nutritional literacy (INL) (AOR=0.17; 95% CI: 0.03–0.82; p=0.027), and critical nutrition literacy (CNL) (AOR=0.03; 95% CI: 0.003–0.327; p=0.004). The main NL protective factors in girls were INL (AOR=0.20; 95% CI: 0.05–0.71; p=0.013) and CNL (AOR=0.27; 95% CI: 0.08–0.95; p=0.043), after controlling for potential confounding variables. Therefore, gender-specific public health strategies are required to prevent overweight.